Synthesis and characterization of novel azo-bridged Zn(II) and Co(II) bisphthalocyanines - (:unkn) unknown (SOC PORPHYRINS & PHTHALOCYANINES, 2006)
Metal phthalocyanines containing an unsymmetrically substituted nitro group were synthesized from 4-nitrophthatonitrile and the corresponding anhydrous metal salts (Co(OAc)(2), Zn(OAc)(2)) by the method of statistically mixed condensation reactions. The new type of metallobisphtlialocyanine compounds connected by a N=N bridge was prepared from the reactions of respective nitro compounds with sodium hydroxide (NaOH) and activated zinc powder in a mixture of methanol (MeOH) and tetrahydrofuran (THF). The structures of these compounds were characterized by using H-1 NMR, IR, elemental analyses, UV-vis and magnetic circular dichroism spectroscopies. Copyright (c) 2006 Society of Porphyrins & Phthalocyanines.
Keywords: phthalocyanine; azo bridge; magnetic circular dichroism; cobalt; SANDWICH DILUTETIUM TETRAPHTHALOCYANINE; LIGHT-EMITTING-DIODES; SUBSTITUTED PHTHALOCYANINES; THIN-FILMS; INTERFACE; PHOTOSENSITIZERS; MACROCYCLES; COMPLEXES; CATALYSTS; CRYSTALS